Multi-dimensional Operators with Sonine Kernels - Fernandez, Arran (Springer Science and Business Media Deutschland GmbH, 2025)
The theory of general fractional calculus with Sonine kernels has been well developed by Luchko in the one-dimensional case. Inspired by recent work on Mikusi?ski’s operational calculus for fractional partial differential operators, we construct a multi-dimensional version of the theory of Sonine kernels. Starting from a generalised version of the classical Sonine convolution condition, we construct fractional integral and derivative operators in arbitrary dimensions, and examine their properties such as fundamental theorems of fractional calculus. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Fractional calculus; Fractional PDEs; Partial differential operator; Sonine kernels